Sensor Mobility Control for Multitarget Tracking in Mobile Sensor Networks. (23rd March 2014) - Fu, Yinfei; Yang, Le
In emerging tracking systems using mobile wireless sensor networks, sensor mobility management is essential for balancing the tracking performance and costs under limited network resources and sensor movements. This paper considers the sensor mobility control problem for multitarget tracking (MTT), in which multiple mobile sensors are dynamically grouped and moved to track multiple targets and collaborate within each sensor group via track data fusion. A novel sensor mobility control framework for the mobile sensor network-based MTT is proposed. It is formulated as a constrained optimization problem that aims to maximize the overall tracking performance for all targets while conserving network energy and providing tracking coverage guarantee. The optimization problem is relaxed as a convex programming problem for computational tractability and its solution is implemented in a distributed manner. The newly proposed sensor mobility control scheme, implemented on the basis of iterative subgradient search, is shown via computer simulation to have better performance over the static sensor network-based MTT.